A conserved poxvirus NLPC/P60 superfamily protein contributes to vaccinia virus virulence in mice but not to replication in cell culture - Senkevich, Tatiana G. (2008)
Of the vaccinia virus genes that are conserved in all sequenced poxviruses, each one except for VACWR084 (G6R) has been at least partially characterized. The poxvirus protein encoded by G6R belongs to the NLPC/P60 superfamily, which consists of proteins with a papain-like fold and known or predicted protease, amidase or acyltransferase activity. The G6 protein was synthesized late in infection and localized to the interior of virions, primarily between the membrane and core. Unlike other conserved poxvirus genes, G6R was not required for virus propagation and spread in a variety of cells. Nevertheless, G6R null mutants caused less severe disease in mice than the parent or revertant virus. Moreover, mutation of the predicted catalytic cysteine led to the same level of attenuation as a null mutant, suggesting that the G6 protein has enzymatic activity that is important in vivo. Conservation of G6R amongst poxviruses and the disparity between its role in vitro and in vivo imply that the protein is involved in an aspect of the virus-host interaction that is common to vertebrates and insects.